IMPROVING STUDENTS' WRITING ABILITY IN DESCRIPTIVE TEXT THROUGH ANIMATED FILM IN CLASS VIII SMP NEGERI 6 PADANGSIDIMPUAN - Khairunnisah, Shoufi Nisma Dewi, Rahmalia Sihite, Happy Sri Rezeki Purba (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The aim of this research is to determine students' ability to write descriptive texts using animated films in class VIII SMP Negeri 6 Padangsidimpuan, and to determine the improvement in students' writing abilities in descriptive texts using animated films in class VIII SMP Negeri 6 Padangsidimpuan. The problem in this research is that students have difficulty generating their ideas, understanding grammar, and lacking vocabulary. This research uses a quantitative and qualitative approach. To collect data, researchers used quantitative and qualitative techniques. Quantitative data was collected through tests consisting of a pre-test and post-test. And qualitative data was collected through interviews and documentation. The design of this research was experimental, the research was held at SMP Negeri 6 Padangsidimpuan. The sample for this research was students in class VIII-2 of SMP Negeri 6 Padangsidimpuan, consisting of 25 students. The average Pre-test score is 59.12 and the average Post-test score is 91.52.Â Based on the explanation above, students' ability to write descriptive text in class VIII of SMP Negeri 6 Padangsidimpuan is categorized as good and through animated films it can make students active and confident in writing.